Early electroacupuncture treatment ameliorates neuroinflammation in rats with traumatic brain injury. Issue 1 (December 2016) - Tang, Wei-Chen; Hsu, Yao-Chin; Wang, Che-Chuan; Hu, Chiao-Ya; Chio, Chung-Ching; Kuo, Jinn-Rung
Abstract Background Neuroinflammation is the leading cause of neurological sequelae after traumatic brain injury (TBI). The aim of the present study was to investigate whether the neuroprotective effects of electroacupuncture (EA) are mediated by anti-neuroinflammatory effects in a rat model of TBI. Methods Male Sprague-Dawley rats were randomly divided into three groups: sham-operated, TBI control, and EA-treated. The animals in the sham-operated group underwent a sham operation, those in the TBI control group were subjected to TBI, but not EA, and those in the EA group were treated with EA for 60 min immediately after TBI, daily for 3 consecutive days. EA was applied at the acupuncture points GV20, GV26, LI4, and KI1, using a dense-dispersed wave, at frequencies of 0.2 and 1 Hz, and an amplitude of 1 mA. Cell infarction volume (TTC stain), neuronal apoptosis (markers: TUNEL and Caspase-3), activation of microglia (marker: Iba1) and astrocytes (marker: GFAP), and tumor necrosis factor (TNF)-α expression in the microglia and astrocytes were evaluated by immunofluorescence. Functional outcomes were assessed using the inclined plane test. All tests were performed 72 h after TBI. Results We found that TBI-induced loss of grasp strength, infarction volume, neuronal apoptosis, microglial and astrocyte activation, and TNF-α expression in activated microglia and astrocytes were significantly attenuated by EA treatment. Conclusions Treatment of TBI in the acute stage with EA for 60 min daily for 3 days could ameliorate neuroinflammation. This may thus represent a mechanism by which functional recovery can occur after TBI.